Arabidopsis thaliana SEPALLATA3 protein prokaryotic expression and purification - He, Q.; Fu, A. Y.; Zhang, G. C.; Li, T. J.; Zhang, J. H. (Cellular and Molecular Biology, 2015)
SEPALLATA3 (SEP3) can be attributed to E class gene of the ABCE model of floral organ development. In order to reveal how SEP3 proteins form polymers, and the relationship between the polymers and their biological functions, the experiments of Arabidopsis thaliana AtSEP3 protein soluble expression in vitro were performed to construct a vector of prokaryotic expression, and investigate induced expression of recombinant proteins in Escherichia coli cells. The protein soluble expression was analyzed through the aspects of different protein domains, induction time, induction temperature, etc. Different structural domains and expression conditions were screened, and 0.1% IPTG inducing at 22 oC for 15 h was estimated as an optimal expression strategy. The nickel chelating resin was used to purify the protein in size exclusion chromatography (SEC) and the results indicated that AtSEP3 protein was present in the form of tetramer.